2011
DOI: 10.1186/1477-7819-9-69
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality treatment of brain metastases: an institutional survival analysis of 275 patients

Abstract: BackgroundWhole brain radiation therapy (WBRT), surgical resection, stereotactic radiosurgery (SRS), and combinations of the three modalities are used in the management of patients with metastatic brain tumors. We present the previously unreported survival outcomes of 275 patients treated for newly diagnosed brain metastases at Cancer Care Northwest and Gamma Knife of Spokane between 1998 and 2008.MethodsThe effects treatment regimen, age, Eastern Cooperative Oncology Group-Performance Status (ECOG-PS), primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Retrospectively, SRS treatment relative to WBRT was associated with a higher risk of LMD occurrence as per Hsieh et al [18] (HR:2.44; 95%-CI:1.15–5.18) and Patel et al [24] (HR:5.67; 95%-CI: 1.50–21.51).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Retrospectively, SRS treatment relative to WBRT was associated with a higher risk of LMD occurrence as per Hsieh et al [18] (HR:2.44; 95%-CI:1.15–5.18) and Patel et al [24] (HR:5.67; 95%-CI: 1.50–21.51).…”
Section: Resultsmentioning
confidence: 56%
“…In their 2011 institutional study, Elaimy et al retrospectively compared six different treatment regimens in patients with metastatic lesions in the brain [24]. Using SRS only as a reference, they found that 15 selected patients treated with SRS following resection had a 68% lower risk of death as compared to 65 patients treated with SRS alone ( p  = 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…Current therapeutic options include neurosurgery, radiosurgery, whole‐brain radiation, and chemotherapy. Patients treated with neuro‐ or radiosurgery appear to have a longer median survival of about 9 months . Chemotherapeutic agents such as temozolomide that are used for treating primary brain tumors are not effective for cerebral melanoma metastases .…”
Section: Introductionmentioning
confidence: 99%
“…ough the literature is inconclusive about the most effective use, radiotherapy is a good adjuvant treatment before or after surgery in more complex conditions, such as in the case of an incomplete resection or if the tumor is inoperable. We have previously published clinical outcomes after radiosurgery or whole brain radiation for brain metastasis of various histologic types [19,20]. Radiation therapy is especially utilized in cases with malignant SFT, narrow margins, tumor size greater than 10 cm, and fast-growing tumors [2].…”
Section: Discussionmentioning
confidence: 99%